The effect of creep feed and diet complexity on growth performance in suckling and weaned pigs - Isensee, Paige K.; Albers, Sarah E.; Wichman, Lindsey G.; Thoma, Autumn L.; Jang, Young D. (Revista Colombiana de Ciencias Pecuarias, 2020)
Background: Creep feed is offered to suckling piglets to introduce solid feed and provide extra nutrients in late lactation. However, the effect of creep feed is inconsistent; there is little information about the effect of creep diet complexity on piglet performance. Objective: Two experiments were conducted to evaluate the effect of creep feed and its complexity on growth performance of suckling and weaned pigs. Methods: In Exp. 1, eight litters (average 19.9 ± 1.1 d of age; initial piglet weight: 6.74 ± 1.2 kg) were allotted to two dietary treatments considering breed, litter size and weight, as follows: no creep feed (n=3) and creep feed (n=5; offered for 8 days before weaning). At weaning (d 28 of age), the pigs were divided into three treatments (6 pigs/pen, 3 replicates; initial body weight: 9.66 ± 0.34 kg) balanced by gender, body weight, and breed, as follows: creep feed eaters, creep feed non-eaters, and no creep feed. In Exp. 2, two different types of creep feed were offered to suckling piglets (initial piglet weight: 3.79 ± 0.55 kg) in seven litters from d 12 of age (average 12.0 ± 1.3 d of age) to weaning (d 25 of age). Treatments were: HCF (n=4): highly-complex creep diet containing 3% fish meal, 2.4% blood meal, and 15% whey; and 2) LCF (n=3): lowly-complex creep diet without the mentioned ingredients. At weaning, only eater pigs were divided into 2 treatments (6 pigs/pen, 3 replicates; initial body weight: 7.53 ± 0.97 kg) balanced by gender, breed and body weight as follows: HCF eaters and LCF eaters. In both experiments, creep feed was mixed with 1% Cr2O3 to measure fecal color for eater/non-eater categorization and the pigs were fed a common nursery diet for 21 days. Results: In both experiments, there were no differences on piglet weaning weight and overall nursery growth performance among the treatments. In Exp. 2, the creep feed intake and percentage of eaters per litter were not different between the HCF and LCF treatments, whereas the HCF eaters tended to have a greater average daily gain (p=0.08) and gain to feed ratio (p=0.09) than the LCF eaters during d 7-14 postweaning. Conclusion: Creep feed did not affect overall piglet growth in suckling and nursery phases, but its complexity might affect pig growth in the early nursery phase.